1999
DOI: 10.1021/jo9815756
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Aryl Methyl Sulfoxides by Oxo(salen)manganese(V) Complexes and the Reactivity−Selectivity Principle

Abstract: The oxidation of various para-substituted phenyl methyl sulfoxides with several substituted oxo(salen)manganese(V) complexes follows an overall second-order kinetics that is first-order in sulfoxide and in oxo(salen)manganese(V) complex. Electron-releasing substituents in sulfoxides and electron-withdrawing substituents in oxo(salen)manganese(V) complexes enhance the rate of oxidation. The less nucleophilic sulfoxides are more sensitive to substituent effect (ρ = −2.44) compared to the corresponding sulfides (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 39 publications
7
53
0
Order By: Relevance
“…However, in the oxidation of phenyl methyl sulfoxides by dioxiranes [34] (ρ = −0.76), gemdialkylperoxonium ion [35] (ρ = −0.83), Cr(VI)-oxalic acid [36] (ρ = −0.93), methyltrioxorhenium(VII) catalyzed H 2 O 2 [43] (ρ = −0.65), and oxo(phosphine)ruthenium(IV) complexes [44] (ρ = −0.42), although low ρ-values have been observed, an S N 2 mechanism has been postulated. In the present study, since the observed ρ-value is high, similar to the ρ-value (−2.44) observed for PhIO oxidation of sulfoxides catalyzed by (salen)Mn III complexes [10] and log k 2 values are better correlated with σ p than σ + /σ + , one may anticipate an S N 2 mechanism involving the ratedetermining electrophilic attack of the oxidant on the sulfur of the sulfoxide. The positive ρ-value of 0.50 ± 0.01 obtained from the Hammett correlation of log k 2 versus 2σ p (Fig.…”
Section: Mechanism Of the Oxygen Atom Transfer From Oxomanganese(v) Tsupporting
confidence: 87%
See 4 more Smart Citations
“…However, in the oxidation of phenyl methyl sulfoxides by dioxiranes [34] (ρ = −0.76), gemdialkylperoxonium ion [35] (ρ = −0.83), Cr(VI)-oxalic acid [36] (ρ = −0.93), methyltrioxorhenium(VII) catalyzed H 2 O 2 [43] (ρ = −0.65), and oxo(phosphine)ruthenium(IV) complexes [44] (ρ = −0.42), although low ρ-values have been observed, an S N 2 mechanism has been postulated. In the present study, since the observed ρ-value is high, similar to the ρ-value (−2.44) observed for PhIO oxidation of sulfoxides catalyzed by (salen)Mn III complexes [10] and log k 2 values are better correlated with σ p than σ + /σ + , one may anticipate an S N 2 mechanism involving the ratedetermining electrophilic attack of the oxidant on the sulfur of the sulfoxide. The positive ρ-value of 0.50 ± 0.01 obtained from the Hammett correlation of log k 2 versus 2σ p (Fig.…”
Section: Mechanism Of the Oxygen Atom Transfer From Oxomanganese(v) Tsupporting
confidence: 87%
“…Acetonitrile (GR, E. Merck) was first refluxed over P 2 O 5 for 5 h and then distilled. The [(salen)Mn III ] + PF 6 − complexes la-f were synthesized according to reported procedure [10,18]. The results of IR and UV-visible spectral studies of all the complexes were found to be identical with literature data [18].…”
Section: Methodsmentioning
confidence: 59%
See 3 more Smart Citations